The Relationship between MELD Score, Bilirubin, Albumin, and INR Levels and Prognosis in Patients with Hepatic Encephalopathy in the Emergency Department - Hızır Ufuk Akdemir; Yahya Şahin (Düzce Tıp Fakültesi Dergisi)
Aim: This study aimed to evaluate the relationship between prognosis and model for end-stage liver disease (MELD) score, albumin, bilirubin, and international normalized ratio (INR) levels in patients diagnosed with hepatic encephalopathy (HE) based on Child-Pugh staging.Material and Methods: This prospective observational study included a total of 49 patients diagnosed with cirrhosis of the liver who presented to the emergency department due to HE. Clinical findings and laboratory values of the patients were prospectively recorded. Each patient's Child-Pugh score, MELD score, INR, albumin, total and direct bilirubin levels were determined and compared according to the Child-Pugh stage.Results: Of the 49 patients included in the study, 32 (65.3%) were male and 17 (34.7%) were female, and the median age was 57 (range, 46-85) years. Of the patients, 28 (57.1%) were in Child-Pugh stage B, and 21 (42.9%) were in Child-Pugh stage C. The most commonly observed encephalopathy symptoms were ataxia (93.9%, n=46) and amnesia (81.6%, n=40). MELD score, INR, and bilirubin levels were found significantly higher in the Child-Pugh C group compared to the Child-Pugh B group (p